1978
DOI: 10.1073/pnas.75.9.4379
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium reverses inhibitory effects of calcium deprivation on coordinate response of 3T3 cells to serum

Abstract: When animal cells are stimulated to multiply by serum, hormones, or various other unrelated agents added to their culture medium, several early events occur, including acceleration in transport and phosphorylation of substrates (1, 2), energy metabolism (3), and synthesis of differentiated cell products (4, 5). After an extended lag period, the accelerated onset of DNA synthesis becomes manifest (6). This array of events has been designated the coordinate response to distinguish it from the "pleiotypic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…A similar conclusion has been reached by Rubin et al (1978) in cultures of mouse fibroblasts exposed to high magnesium concentrations in a calcium-deprived medium. Magnesium may also exert its stimulatory effects on keratinocyte proliferation by affecting the organization of the cytoskeleton (Howard and Timasheff, 1988) or by improving cell-matrix interactions (Attramadal, 1969;Ruoslahti and Pierschbacher, 1987;Yasuda, 1974).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A similar conclusion has been reached by Rubin et al (1978) in cultures of mouse fibroblasts exposed to high magnesium concentrations in a calcium-deprived medium. Magnesium may also exert its stimulatory effects on keratinocyte proliferation by affecting the organization of the cytoskeleton (Howard and Timasheff, 1988) or by improving cell-matrix interactions (Attramadal, 1969;Ruoslahti and Pierschbacher, 1987;Yasuda, 1974).…”
Section: Discussionsupporting
confidence: 74%
“…As opposed to its effect on mouse epidermal cell cultures, reduction of extracellular calcium (<0.02 mM) markedly inhibited the initiation of DNA synthesis in the fibroblast cell cultures. This inhibition was abolished by increasing the magnesium content of the medium (Rubin et al, 1978). The present results suggest that magnesium, added to a low calcium-containing medium, can complement the reduced calcium in enhancing the proliferation of mouse keratinocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Over the last 40 years, the role of Mg 2ϩ in cell cycle control, protein synthesis, and growth factor response has been extensively studied, pioneered by several groundbreaking studies from the group of Harry Rubin (428,430). Cell proliferation is largely dependent on protein synthesis, more than DNA or RNA synthesis.…”
Section: E Cell Proliferationmentioning
confidence: 99%
“…Early work by Rubin suggested that Ca 2+ and Mg 2+ synergize in cell growth and proliferation [40]. Another group proposed that extracellular Mg 2+ is essential for progression of WI-38 fibroblast from G1 into S phase [41].…”
Section: Introductionmentioning
confidence: 99%